Timeliness in the Supply Chain as Determinant of the Functioning of Logistics Processes - Mieczyslaw PAWLISIAK (Communications of International Proceedings, 2021)
The article attempts to improve the on-time delivery process in a logistics company operating on the domestic and foreign market. Areas requiring modification were identified and in the light of growing problems in the company, modern methods of solving them were proposed. An analysis of the functioning of the examined company was carried out and possible benefits in the supply chain were demonstrated. By forecasting the possible effects, it has also been shown that the application of the proposed solutions may significantly reduce the intensity of the negative impact of the identified problems. As a result of the research, the benefits that the enterprise in question can achieve by modifying one of the logistics processes were indicated. The presented conclusions showed that making sometimes difficult decisions by the company’s management, especially in the area of economic security, supported by effective planning, can bring the expected results.
Keywords: Timeliness; Service Industry; Logistic Processes; Services; Deliveries; Transport.